2013
DOI: 10.1148/radiol.12112077
|View full text |Cite
|
Sign up to set email alerts
|

Pleural and Peripheral Lung Lesions: Comparison of US- and CT-guided Biopsy

Abstract: With pleural or peripheral lung lesions, US guidance is comparable to CT guidance in terms of sample accuracy, while allowing for a significant reduction in procedure time and postprocedural pneumothorax and being free from ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 22 publications
9
113
0
10
Order By: Relevance
“…Overall the diagnostic yield of image guided TTNA biopsy in our study was around 60% which is somewhat lesser than that in reported literature (70-90%). [22] This could be due to the small sample size and/or very stringent conditions of counting a biopsy a success. Moreover, the diagnostic yield is also influenced by the size of the nodule with lobes >2cm giving better definitive diagnosis.…”
Section: Success Rate Of Different Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the diagnostic yield of image guided TTNA biopsy in our study was around 60% which is somewhat lesser than that in reported literature (70-90%). [22] This could be due to the small sample size and/or very stringent conditions of counting a biopsy a success. Moreover, the diagnostic yield is also influenced by the size of the nodule with lobes >2cm giving better definitive diagnosis.…”
Section: Success Rate Of Different Imaging Modalitiesmentioning
confidence: 99%
“…[20,21] Ultrasound guided TTNA biopsies are generally well tolerated probably because lung lesions guided by ultrasounds are peripheral in nature with less chances of pneumothorax. [22] …”
Section: Introductionmentioning
confidence: 99%
“…The patient is placed in a lateral decubitus or, rarely, prone position and a low-frequency (2-5 MHz) curvilinear probe employed to direct the core-cutting biopsy needle, having first identified any underlying at-risk structures including intercostal vessels [38] and viscera. The technique permits, in expert hands, the sampling of not only pleural abnormalities but also chest wall and peripheral lung parenchymal lesions for diagnostic purposes [103,104]. Whilst no formal guidelines exist, the authors would suggest performing between eight and 10 core pleural biopsies to ensure adequate sampling.…”
Section: Medical Thoracoscopy and Closed Pleural Biopsymentioning
confidence: 99%
“…Ultrasound does not entail exposure to ionising radiation, and the equipment is substantially cheaper. In a retrospective review of 273 biopsies of pleural lesions and peripheral lung lesions abutting the pleura, technical success was high with both ultrasound and CT guidance (97.1% and 96.5% respectively) [31]. Procedures using ultrasound were substantially faster and resulted in fewer negative biopsy results.…”
Section: Image-guided Cutting Needle Biopsiesmentioning
confidence: 99%